Fragmentasi Gerakan Buruh di Indonesia Pasca Orde Baru - MURYANTO AMIN (Universitas Sumatera Utara, 2011)
happened because labor organization during the period prohibited to do political activity. The impact is labor organization didn’t have power to influence government policy at labour issue. Since the new order was collapses, labour has become as the political power in politics. Nevertheless that still has not yet become the real power. This Study states its problem is be-cause labour movement organization is fragmented. This Study discusses why this condition can happen. To answer that question, this study uses the approach of relation between state and civil society and use literature study and document in data collecting. The finding is: First, the labor organization in Indonesia haves history burden, especially memory about new order ex-perience that bridles labor movement; The elite of labour movement organization affect different political way, because must follow its political party rule; Last, the labour movement didn't have a movement pattern with tactical and systematic target goals.Keywords: Labour movement, fragmented organization, political participation.